2020
DOI: 10.1002/2211-5463.13051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injured and dead cells of Escherichia coli on the colony‐forming rate of live cells

Abstract: Single‐cell sorting of Escherichia coli was conducted to analyze the effect of osmotic stress–induced injury on the colony‐forming rate (CFR). Injury caused a time delay in the start of colony formation and a decrease in the final level of CFR. Surprisingly, dead cells also inhibited cell growth possibly due to the release of insoluble factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In our laboratory a novel double cultivation method without any selective principles has also been proposed previously for enumeration of the injured cell population (Tsuchido, 2017) . Furthermore, Saito et al (2021) have recently reported the effect of osmotic stress on mated microcolony growth analyzer. The monitoring system can detect microcolonies formed by bacterial cells on each agar medium of a maximum of 100 plates and the threshold size of one microcolony is about 65µm in diameter, although varying with colony shape characteristic for the kinds of bacterial strain and the medium used.…”
mentioning
confidence: 99%
“…In our laboratory a novel double cultivation method without any selective principles has also been proposed previously for enumeration of the injured cell population (Tsuchido, 2017) . Furthermore, Saito et al (2021) have recently reported the effect of osmotic stress on mated microcolony growth analyzer. The monitoring system can detect microcolonies formed by bacterial cells on each agar medium of a maximum of 100 plates and the threshold size of one microcolony is about 65µm in diameter, although varying with colony shape characteristic for the kinds of bacterial strain and the medium used.…”
mentioning
confidence: 99%